Assessment of Electrolytes Level Among Type 2 Diabetes Patients - Dr Sunita Sethi; Dr. Swati D Sawant; Dr Kamalakar Mane; Dr Yasmeen Mukthar (International Journal of Pharma and Bio Sciences, 2023)
Diabetes mellitus(DM) is a global public health concern that is considered by prolonged hyperglycemia triggered by compromised insulin action or secretion. Numerous studies have shown a link between electrolyte intensities and diabetes. Therefore, this study aimed to investigate the association between fasting glucose in plasma and electrolytes and absorption electrolyte imbalances in individuals with type 2 diabetic ailments. High blood sugar (BS) injures the nephrons, affecting electrolyte exchange. The study enrolled 62 participants into two groups: the study group with Type 2 diabetes (Type 2) and consistently high random blood sugar levels (BSL) above 300 and the control group with lower BSLs. The findings suggest that higher blood glucose levels(BGL) are associated with increased potassium and chloride levels. In conclusion, individuals with Diabetes (Type 2) and BGL above 300 exhibits lower levels of sodium but higher serum potassium and chloride levels (PCL) compared to those with lower BGL. The study’s results shed light on the potential electrolyte imbalances in individuals with Diabetes (Type 2), particularly those with poorly controlled BGL. Understanding these imbalances is crucial for healthcare providers to manage and treat diabetic patients effectively. This study provides valuable insights into the relationship among fasting plasma glucose (FPG), electrolyte levels, and Diabetes (Type 2). Further research is warranted to elucidate the underlying mechanisms and potential clinical implications of these electrolyte imbalances in individuals with diabetes.